الاختلاف النسبِي وأثره في تقويم الأعمال والأشخاص : دراسة حديثية - خليفات، إسلام بن صالح (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research highlights the impact of relativistic differences between the people and their circumstances and conditions while we evaluate them or evaluate their actions, and the effect of differentiation between them. The research also attempts to confirm the authenticity of this principle in Islam through extrapolation of Qur'anic verses and a large numbers of Al Ahadith al-Nabawia that are related to the topic of this study and how Islam contemplates those differences and the relative disparity during the evaluation process. Subsequently, I chose some of those Qur'anic verses and Hadiths which are documented and evaluated by the researcher as religious evidence to prove that Islam is interested in this principle (relative evaluation) and use it in several fields of human beings life through an analytical method for those religious texts to determine the indication of this principle, or how they testify this, enlightened by opinions of scholars and some meditation peppered with criticism and commentary. Moreover, the research highlights the most important values that Islam considers through this relative evaluation and tries to connect them with it like justice, realistic, moderation and other values. Finally, the research discusses some of the fields that we can apply in this relative criterion during the evaluation process in our daily lives such as evaluation of the gift and evaluation of its owners, evaluation of bravery of the scholars to tell the truth, and evaluation of the people's morals and behaviours, as practical models which other fields can measure by.